Identification of Methicillin-Resistant Staphylococcus aureus (MRSA) carriers in the nasal passages of healthcare workers at Universitas Udayana Hospital - Winaya, Made Illene; Made Agus Hendrayana; Ni Nyoman Sri Budayanti; Ni Nengah Dwi Fatmawati (Journal of Clinical Microbiology and Infectious Diseases, 2025)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) is a major pathogen responsible for healthcare-associated infections (HAIs), with growing global concern due to its resistance to multiple antibiotics, including beta-lactams. Healthcare workers (HCWs), particularly those in critical care settings, are at risk of being asymptomatic carriers, facilitating MRSA transmission. This study aimed to determine the prevalence and distribution of MRSA carriers among healthcare workers (HCWs) at Universitas Udayana Hospital, Bali, Indonesia. Methods: A descriptive cross-sectional study was conducted from October to November 2024. A total of 44 nasal swab samples were collected from nurses across various hospital wards. Samples were cultured on Mannitol Salt Agar and underwent Gram staining, catalase, and coagulase testing. MRSA identification was confirmed using the cefoxitin disk diffusion method, with inhibition zones of ≤21 mm indicating methicillin resistance, as per CLSI guidelines. Data were analyzed descriptively. Results: MRSA colonization was identified in 4 out of 44 samples (9.1%), with cases distributed in the NICU (2 cases), ICU (1 case), and Surgical Ward (1 case). In addition, 12 samples (27.3%) were positive for methicillin-sensitive Staphylococcus aureus (MSSA), while 28 samples (63.6%) contained coagulase-negative staphylococci (CNS), predominantly in the outpatient and emergency departments. Conclusion: The presence of MRSA among HCWs, especially in critical units like NICU and ICU, emphasizes the importance of enhanced infection control measures. Routine screening, strict adherence to hand hygiene, appropriate use of personal protective equipment, and implementation of decolonization protocols, such as mupirocin application and chlorhexidine bathing, should be optimized to reduce MRSA transmission risks within healthcare facilities.